Antibiotic Potential and Biophysical Characterization of Amphipathic β-Stranded [XZ]n Peptides With Alternating Cationic and Hydrophobic Residues - Strandberg, Erik; Wadhwani, Parvesh; Ulrich, Anne S. (Frontiers in Medical Technology, 2021)
Cationic membrane-active peptides are considered to be promising candidates for antibiotic treatment. Many natural and artificial sequences show an antimicrobial activity when they are able to take on an amphipathic fold upon membrane binding, which in turn perturbs the integrity of the lipid bilayer. Most known structures are α-helices and β-hairpins, but also cyclic knots and other irregular conformations are known. Linear β-stranded antimicrobial peptides are not so common in nature, but numerous model sequences have been designed. Interestingly, many of them tend to be highly membranolytic, but also have a significant tendency to self-assemble into β-sheets by hydrogen-bonding. In this minireview we examine the literature on such amphipathic peptides consisting of simple repetitive sequences of alternating cationic and hydrophobic residues, and discuss their advantages and disadvantages. Their interactions with lipids have been characterized with a number of biophysical techniques—especially circular dichroism, fluorescence, and infrared—in order to determine their secondary structure, membrane binding, aggregation tendency, and ability to permeabilize vesicles. Their activities against bacteria, biofilms, erythrocytes, and human cells have also been studied using biological assays. In line with the main scope of this Special Issue, we attempt to correlate the biophysical results with the biological data, and in particular we discuss which properties (length, charge, aggregation tendency, etc.) of these simple model peptides are most relevant for their biological function. The overview presented here offers ideas for future experiments, and also suggests a few design rules for promising β-stranded peptides to develop efficient antimicrobial agents.